Severe Hereditary Deficiency of Factor VII during Pregnancy - Seligsohn, U; Peyser, M. R; Toaff, R; Shani, M; Ramot, B (Thrombosis and Haemostasis, 1970)
In normal pregnant women factor VII level is increased. This may also be observed in women with hereditary partial factor VII deficiency.In a 38 year old woman with severe hereditary factor VII deficiency no change of the factor level was observed during pregnancy. The patient underwent two uneventful caesarian sections because of placenta praevia and transverse lie of the fetus.During the second caesarian section factor VII level was simultaneously determined in blood obtained from the antecubital and uterine veins and from the umbilical vein and artery. Factor VII levels in the umbilical vessels were similar and exceeded the levels observed in the mother’s vessels. In 3 control patients similar examinations were performed during caesarian sections but reversed ratios of factor VII levels were observed. These data seem to prove that factor VII does not cross the placenta.In the family study 2 siblings were found to have severe factor VII deficiency whereas several other members had either normal or partial deficient levels. The results obtained support again the assumption that factor VII deficiency is inherited by an autosomal gene that in the homozygous state is manifested by severe factor VII deficiency and in the heterozygous state by mild deficiency or normal factor VII levels.